Tinjauan Hukum Islam Terhadap Bagi Hasil Penggarapan Tanah Sawah Di Desa Palur Kecamatan Mojolaban Kabupaten Sukoharjo - Zahiruddin, Febrianzah (2016)
Communities in the District Mojolaban Palur village of Sukoharjo are the majority of farmers, especially in the agricultural sector (muzara'ah), in addition to managing their own fields, also employ others to work on the fields with a profit-sharing system in accordance with the agreements or local customs. In general, this cooperation is based on an agreement or a trust between the two sides and with a contract verbally, thus giving opportunities between the two sides do things that can be detrimental, as the contents of the agreement, the rights and obligations of both parties, the distribution of the results is not necessarily equally and in accordance with the principles of Islamic law. From where authors try to trace and examine whether the implementation of the results in the Palur village there is fraud and the exploitation of one party against another party. The matters discussed in this thesis is about the procedure and the execution of the contract muzara'ah seen from a review of Islamic law. In writing this skirpsi, the type of research that is used compiler is field research, to solve the problems faced by urf normative approach was used, so that with such an approach is expected compilers can assess whether the implementation of the results in the Village Palur appropriate or not according to Islamic law. While the data obtained comes from the actors for results and Palur village communities that are considered to understand and know about the issue, but it is also of the data in the form of relevant literature. Based on the study, authors concluded that the implementation of the results conducted in the village of Palur already legal under Islamic law. Such cooperation including in the field of muzāra 'ah, because the terms and rukunnya have been met, as well as the results are already fulfill the law of Islam.